The Decision Support System For The Acceptance of Pencak Silat Athletes in Pra-PON and PUSLATDA Team Selection Using Technique For Other Preference By Similarity To Ideal Solution Method - Mochammad Rizaldy; Achmad Muchayan; Made Kamisutara (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
Pencak Silat is one of the traditional martial arts that originated from Indonesia. The parent of Pencak Silat organization in Indonesia is INDONESIAN PENCAK SILAT ASSOCIATION (IPSI). Pencak Silat is one of the most reliable sports branches at the International-scale Olympics. Proven at the ASEAN GAMES 2018 Olympics and then the Pencak Silat Sports Branch is one of the sports branch of the most gold medal with a total of 14 medals. With the increasingly tight competition of Pencak Silat Sports, the trainer desperately needs athletes who fit certain criteria in order to be reliable in a tournament. In this study aims to assist the trainer in selecting athletes that correspond to the criteria. Therefore, a decision support system is required to assist the trainer in selecting qualified athletes. In this research, using the Technique for Other Preference by Similarity To Ideal Solution method is used to advise athletes who are eligible to be contested according to the calculation result. Result system of decision support system with Topsis method of this research has been tested by Pencak Silat Trainer and produce the results of the selection that is expected by the trainer. Keywords: Pencak Silat, Decision Support Systems, Technique For Other Preference by Similarity To Ideal Solution, Web